(untitled) (Journal of Imam Al-Kadhim College, 2025)
Through the examination of the extract of the play ’ The Tempest’ in Iraqi Secondary schools, this paper explores the depictions of colonial and cultural identities within this work in the book entitled ’ English for Iraq’. The paper challenges the domination of narratives and how they express the characterization and themes in the extract to form a colonial experience of Iraqi students’ history and culture. This colonial ideology is hidden in Prospero’s and Caliban’s speeches. The aim of this paper explore a complex interface between the colonial strategy and Iraqi students’ understandings, emphasizing the necessity of utilizing such a decolonial vision that enables us to make scrutiny and evaluation of the colonial impacts on Iraqi students’ identities and experiences The paper applies Edward Said’s contrapuntal mode of reading on the extract to gain this decolonial vision. The mode has two stages of analysis. The examination and exposition of the extract are done in the first stage, and the discussions of juxtapositional analysis lie in the second stage. The contribution of this study revolves around the decolonization of literary texts on the academic level. Ultimately, the mode provides the vision that helps the progress of Iraqi students’ critical thinking about social justice and Iraqi cultural identity in Iraqi secondary schools.